Impact of Digital Innovations on Business Competitiveness and Sustainability – A Data-Driven Approach - Priandito; Ramadan, Ahmad; Kuusk, Taavi (Pandawan, 2025)
This study examines the critical interplay between digital innovations, business competitiveness, and sustainability, providing empirical evidence on their inter- connections. Digital innovations, encompassing technologies such as artificial intelligence (AI), blockchain, and the Internet of Things (IoT), have emerged as transformative forces driving efficiency and enabling sustainable practices. The research employs a quantitative design, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from diverse organi- zations. Results confirm that digital innovations significantly enhance busi- ness competitiveness, which in turn mediates their positive impact on sustain- ability outcomes. The findings underscore the necessity for strategic align- ment of technological adoption with business objectives to achieve competitive differentiation and meet sustainability goals. Key insights reveal that sector- specific strategies are essential for maximizing the benefits of digital transfor- mation. Manufacturing benefits from predictive maintenance, retail achieves supply chain transparency, finance leverages blockchain for ESG reporting, and technology focuses on scalable, sustainability-integrated solutions. The study also highlights the role of supportive regulatory frameworks and cross-sector collaboration in fostering innovation and sustainability. These insights con- tribute to academic discourse and provide actionable guidance for policymak- ers and industry leaders. Future research should explore longitudinal impacts and cross-industry dynamics to deepen the understanding of digital innovations’ role in sustainable economic growth.